Guidelines for Introducing Industrial Robots to Replace Manufacturing Workforce to Enhance Competitiveness in the Digital Era - Naranchala Khumlaitong; Taweesak Roopsing; Thanin Silpcharu (Migration Letters, 2023)
Industrial robots have replaced manufacturing labor efficiently, improving production processes and technology, enhancing competitiveness, and creating opportunities to reduce labor costs, production time, and increase product quality. This research aims to develop a structural equation model for the effective substitution of manufacturing labor with industrial robots using mixed methodology research. Qualitative data from 9 experts and 11 successful businesspersons were used to refine the model, while quantitative data from 500 industrial sector managers with granted patents were analyzed through descriptive, inferential, and multivariate tests. The research found that the components of an effective problem-solving approach include 1) Production potential ( = 4.15), emphasizing suitable technology and innovation evaluation, 2) Industrial readiness ( = 4.10), stressing clear organizational vision and production policy, 3)Integration of cooperation( = 4.07), highlighting collaboration for knowledge exchange, and 4) Government Policies and promotions ( = 4.04), emphasizing compliance with government policies. Hypothesis testing found no significant difference between medium and large businesses in adopting industrial robots as labor substitutes in production. The model met evaluation standards and empirical data consistency, indicating strong potential for application (chi-square probability = 0.079, chi-square coefficient = 1.130, congruence coefficient = 0.956, root mean square deviation index = 0.016).